An optoelectronic nose for identification of explosives. Issue 1 (7th October 2015) - Askim, Jon R.; Li, Zheng; LaGasse, Maria K.; Rankin, Jaqueline M.; Suslick, Kenneth S.
Abstract : A portable optoelectronic nose for the identification of explosives uses a highly cross-reactive colorimetric sensor array and a handheld scanner. Abstract : Compact and portable methods for identification of explosives are increasingly needed for both civilian and military applications. A portable optoelectronic nose for the gas-phase identification of explosive materials is described that uses a highly cross-reactive colorimetric sensor array and a handheld scanner. The array probes a wide range of chemical reactivities using 40 chemically responsive colorimetric indicators, including pH sensors, metal–dye salts, redox-sensitive chromogenic compounds, solvatochromic dyes, and other chromogenic indicators. Sixteen separate analytes including common explosives, homemade explosives, and characteristic explosive components were differentiated into fourteen separate classes with a classification error rate of <1%. Portable colorimetric array sensing could represent an important, complementary part of the toolbox used in practical applications of explosives detection and identification.